The study of the chinese character "mei" (美) From the perspectives of chinese character creation / Wong Hoong Cheong, Goh Ying Soon & Yap Soh Leay - Wong, Hoong Cheong; Goh, Ying Soon; Yap, Soh Leay (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
The Chinese character "mei"(美) carries out the meaning of beauty in Chinese. However, Shuowen Jiezi (《说文解字》) had denoted the meaning of “mei” as sweetness (甘) during the East Han dynasty, but there are still lots of arguments concerning the meaning of this Chinese character “mei” until now. Even though, the creation method of the Chinese character “mei” is a topic that had been explored by many researchers and scholars, they still fail to agree on one particular idea only for this character. Majority scholars divided character "mei" into upper and lower parts in their explanation or findings. The lower part of "mei" was recognized by majority scholars as “大” (da, big) or “ 人 ” (ren, human being). Yet, the controversial part was the upper part as there were various interpretations made by scholars on it namely goat, horns of goat, feather wearing, head ornaments, panache and etc. The unearthed artifacts and archaeological finds were presented as focuses of discussion. In giving contributions to the teaching and learning of Chinese linguistics courses such as etymology, ancient Chinese philology as well as related courses, the discussions in this paper is able to shed some lights.